IMPLEMENTASI LINGUISTIK TENTANG GENDER DALAM ALQUR’ÂN TERHADAP HUKUM ISLAM - Bustami Saladin (IAIN MADURA, 2011)
Arabic has an important position in Islamic studies, in the development of Arabic, the language al-Qur'ân can be classified into classical Arabic, the language al-Qur'ân which developed into a literary language since the 7th century AD. Thanks to the altitude of the language al-Qur'ân precisely then that the experts make the standardization of the Arabic language is academic in the 3rd century H (9 M) and 4 H (10 M). In the process of standardization is determined systematics grammatikal, syntax, vocabulary, and the use of literature through a variety of in-depth research activities Arabic has an important position in Islamic studies, in the development of Arabic, the language al-Qur'ân can be classified into classical Arabic, the language al- Qur'ân which developed into a literary language since the 7th century AD. Thanks to the altitude of the language al-Qur'ân precisely then that the experts make the standardization of the Arabic language is academic in the 3rd century H (9 M) and 4 H (10 M). In the process of standardization is determined systematics grammatikal, syntax, vocabulary, and the use of literature through a variety of in-depth research activities